2014
DOI: 10.4103/1119-3077.130226
|View full text |Cite
|
Sign up to set email alerts
|

Facial soft tissue changes after orthodontic treatment

Abstract: There were significant changes in facial soft tissue esthetics after orthodontic treatment for class II and III cases. Changes in A-N-B and nose tip angle (N-Pn-Cm) were observed for class II and class III subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Many soft tissue cephalometric norms have been reported in the literature to diagnose and curate treatment keeping in mind the facial esthetics [12][13][14]. Soft tissue changes after orthodontic treatment have been extensively assessed by many authors [15][16][17]. Recently, studies have reported assessing soft tissue profiles with photographs and silhouettes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Many soft tissue cephalometric norms have been reported in the literature to diagnose and curate treatment keeping in mind the facial esthetics [12][13][14]. Soft tissue changes after orthodontic treatment have been extensively assessed by many authors [15][16][17]. Recently, studies have reported assessing soft tissue profiles with photographs and silhouettes [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Dental malocclusions (MO) represent one of the most frequent dental alterations ( 1, 2 ). Today within the goals of orthodontic treatment in addition to the establishment of ideal skeletal and dental relationships is considered facial aesthetics due to the high aesthetic expectations of patients ( [3][4][5][6] ).…”
Section: Introductionmentioning
confidence: 99%